2015
DOI: 10.1111/bph.13003
|View full text |Cite
|
Sign up to set email alerts
|

The activation of supraspinal GPR40/FFA1 receptor signalling regulates the descending pain control system

Abstract: BACKGROUND AND PURPOSEThe ω-3 polyunsaturated fatty acids exert antinociceptive effects in inflammatory and neuropathic pain; however, the underlying mechanisms remain unclear. Docosahexaenoic acid-induced antinociception may be mediated by the orphan GPR40, now identified as the free fatty acid receptor 1 (FFA1 receptor). Here, we examined the involvement of supraspinal FFA1 receptor signalling in the regulation of inhibitory pain control systems consisting of serotonergic and noradrenergic neurons. EXPERIMEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…17) The inhibitory effect of PCPA on AcAP-induced analgesia in the formalin test is also consistent with the results of an earlier study. 7) Consistent with previous reports, 30,31) the PCPA treatment protocol used in the present study markedly reduced the serotonin content of the central nervous system. The basal rectal temperature of the PCPAtreated mice was normal, suggesting that the lack of serotonin can be compensated by other thermoregulatory mechanisms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…17) The inhibitory effect of PCPA on AcAP-induced analgesia in the formalin test is also consistent with the results of an earlier study. 7) Consistent with previous reports, 30,31) the PCPA treatment protocol used in the present study markedly reduced the serotonin content of the central nervous system. The basal rectal temperature of the PCPAtreated mice was normal, suggesting that the lack of serotonin can be compensated by other thermoregulatory mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…31) Mouse brains were homogenized in the solu- tion containing 0.05% Triton-X and 10 mM ammonium formate (pH 4.0, 1 mL per 100 mg tissue). An equal volume of ice-cold chloroform-methanol (2 : 1, v/v) containing 6.6 µM 3,4-dihydroxybenzylamine hydrobromide (DHBA, Sigma, St. Louis, MO, U.S.A.) as internal standard was added to the homogenate and centrifuged at 1500×g for 30 min at 4°C.…”
Section: Lc-ms/ms Analysis Of Monoamines In the Mouse Brainmentioning
confidence: 99%
“…In our previous study, we demonstrated that pretreatment with GW1100 exacerbates formalin or CFA-induced pain behavior (Nakamoto et al, 2014). Furthermore, we showed that free fatty acid levels rise in the hypothalamus during inflammatory pain induced by CFA (Nakamoto et al, 2013), suggesting that free fatty acids may be continuously released during pain.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, our results indicate that astrocytes might be involved in control of brain FFAs composition respond to LPS stimulation. Based on our previous reports, 32,33) it is thought that these FFAs released from astrocytes might maintain a neuronal function as a ligand of GPR40/FFAR1, one of a FFAs receptors.…”
Section: Discussionmentioning
confidence: 99%